Institutional arrangements for biofuel feedstock production in Zambia - Paul C. Samboko; Cliff Dlamini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Given likely increases in biofuel demand across Southern Africa, we identify suitable production models in Zambia for the Southern African market. This is crucial given, on the one hand, the problems of contract failure and transaction costs that plague outgrower models in Southern Africa and, on the other, the uniqueness of crops with respect to input requirements and characteristics. In this paper, we review existing cash crop production models that can be used for biofuel feedstock production in Zambia with a special focus on sugarcane and seed cotton. We find the organization of the Kaleya, Manyonyo, and Magobbo irrigation schemes as candidate institutional arrangements for bioethanol feedstock production. For biodiesel feedstocks, the Dunavant (NWK Agri-services) distributor model is best suited to increased smallholder participation.
Keywords: L23; O13; N77; O19; Q16; 330; biofuels; feedstocks; institutional arrangements Zambia; Southern Africa